Metal Detecting Sensors: A Review on the Transition from Traditional Sensors to Field-Portable Sensors - Siangproh, Weena; Anekrattanasap, Ananyaporn; Meoipun, Adison (Science Essence Journal, 2023)
Recently, in-situ analyses have been required in a variety of situations for clinical, food, environmental, and industrial samples. Therefore, not only do devices have to be miniaturized, lightweight, affordable, portable, autonomous, reusable, or disposable, but the approaches used must also be straightforward to understand, friendly, and sensitive enough to yield exact and accurate findings. Electroanalytical chemistry concepts have an advantage over other approaches in that they provide inexpensive and efficient ways to handle them. Thus, it is essential for satisfying the continually changing needs of scientific and industrial research. In this review, the use of these electrochemical methods in metal analysis, particularly for toxic metals, and numerous examples that have been described in the literature over the past ten years are discussed. The detail starts with a description of the traditional sensors and is followed by descriptions and explanations of various cutting-edge devices that will become well-known field-portable sensors during this time.